2021
DOI: 10.3390/ijerph18179294
|View full text |Cite
|
Sign up to set email alerts
|

Syndrome Metabolic Markers, Fitness and Body Fat Is Associated with Sleep Quality in Women with Severe/Morbid Obesity

Abstract: Background: Sleep is an important modulator of neuroendocrine function and glucose metabolism. Poor sleep quality is related to metabolic and endocrine alterations, including decreased glucose tolerance, decreased insulin sensitivity, and increased hunger and appetite. Objective: The aim of the present study was to determine the association between sleep quality with metabolic syndrome (MetS) markers, fitness and body fat of women with severe/morbid obesity. Methods: This cross-sectional study included 26 wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
6
0
1
Order By: Relevance
“…The muscle quality index was estimated by HGS divided by BMI. A hydraulic hand dynamometer (BASELINE ® Hydraulic Hand Dynamometers, NY, USA) was used to determine HGS, which has been used previously [11]. The measure of each dominant and non-dominant arm was made in two attempts, and the best result from each was selected.…”
Section: Measurements 221 Muscle Quality Indexmentioning
confidence: 99%
See 1 more Smart Citation
“…The muscle quality index was estimated by HGS divided by BMI. A hydraulic hand dynamometer (BASELINE ® Hydraulic Hand Dynamometers, NY, USA) was used to determine HGS, which has been used previously [11]. The measure of each dominant and non-dominant arm was made in two attempts, and the best result from each was selected.…”
Section: Measurements 221 Muscle Quality Indexmentioning
confidence: 99%
“…Similarly, morbidly obesity (defined by the body mass index (BMI) ≥ 40 kg/m 2 or 35 kg/m 2 with obesity-related health conditions) [10] has been related to the prevalence of CVD, poor subjective well-being, and bad functional capacity [11]. Moreover, metabolic syndrome (MetS) is a cluster of cardiovascular risk factors including abdominal obesity, high blood pressure, high blood glucose, and blood lipid abnormalities [12].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, another study reported a positive relationship between muscle mass and sleep quality [ 50 ]. In the context of morbid and severe obesity, a previous study reported that poor sleep quality had a positive association with several negative outcomes, including body fat percentage, glucose alteration, and poorer HSG [ 51 ]. In addition, in obese subjects, improvements in sleep quality have been reported after participating in a strength program [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that the shorter sleep duration increases the waist circumference and the caloric intake, suggesting that there is a correlation between sleep duration and body composition [15,16]. In addition, these changes in metabolic indicators, including body fat, are also linked to sleep quality [17].…”
Section: Original Articlementioning
confidence: 99%